Bantuan Ekspor dan Faktor-faktor Internal sebagai Anteseden bagi Adaptasi Produk, Keunggulan Bersaing dan Kinerja Ekspor (Studi pada Usaha Kecil dan Menengah di Daerah Istimewa Yogyakarta dan Jawa Tengah) - Siti Dyah Handayani; Ubud Salim; Mintarti Rahayu; Djumahir - (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The primary objectives of this research are to examine and explain the role of export assistance (given by the government) as well as the internal factors (export commitment, satisfaction with prior year’s export performance, management international experience) and to implement product adaptation strategy to create competitive advantage and improving SMEs’ export performance. The design of the research is mixed method. The target population of the research is exporter SMEs of furniture and craft in Yogyakarta and Central Java. The data was collected using questionnaire which involved 130 respondents (net response rate 76.5%), and in-depth interviews which involved 13 informants. The findings of the research do not fully support the contingency approach. The export performance of SMEs is directly influenced by competitive advantage, satisfaction with prior year’s export performance, and export assistance. The competitive advantage is directly influenced by product adaptation strategy, export commitment, and management international experience. Product adaptation strategy implemented by most of SMEs affects the competitive advantage, but it does not promote direct influence to export performance financially. Competitive advantage is a crucial factor for it is able to function as key mediator to support internal factors and product adaptation strategy in improving the export volume, revenue, and profitability. The research findings show that product adaptation strategy and internal factors (commitment and international experience) play bigger roles as antecedent of long term export success which is competitive advantage, while export assistance only functions as antecedent of short term export success which is financial export performance.Keywords: export, SMEs, export assistance, satisfaction, international experience, commitment, product adaptation, competitive advantage, performance.